Agrarian change and economic development : (Methuen & Co., 1969)
Agrarian Change and Economic Development is a landmark volume that examines the historical experience of the relationship between agrarian change and economic development. The essays in this book redress this balance, and illustrate the significance of the western world's escape from an overwhelmingly agrarian condition. It is therefore an ideal work for encouraging those concerned with current problems to perceive agricultural development as professional historians see it, and to question the oversimplified historical analogies commonly employed in development economics.